Five decades of infectious diseases outbreaks in the African region (1970–2018) a geographic snapshot - Roland Ngom; Abdou Salam Gueye; Stephanie Lassieur; Stephen Oloo; Rizwan Shahid; Valerie Mize; Charles Lukoya Okot; Joseph Cabore Waogodo; Ibrahima Socé Fall (Social Sciences and Humanities Open, 2023)
This paper is being written at a time when the recent pandemic, namely COVID-19, has shaken the entire world in a manner that has never been seen in modern history. The ecology, socio-economy and weak health systems make Africa an area favorable to the occurrence of various diseases and disease outbreaks. This paper explores forty-eight (48) years of disease outbreaks in the WHO African region of the World Health Organization (WHO). Twenty-five (25) Integrated Disease Surveillance and Response priority diseases were selected, and their outbreaks were described and analyzed. Using inferential spatial statistics, spatial clusters at the health district level, specifically hot spots of those outbreaks, were produced and analyzed. The Population at risk of those hot spots was estimated. Results show a consistent report of outbreaks during the selected period, with 52 outbreaks on average per year. Poliomyelitis, cholera, yellow fever, meningococcal disease and measles were the most reported outbreaks. Democratic Republic of the Congo (DRC) and Nigeria were the countries reporting the highest number of outbreaks (5 on average per year), with high number of people living in hot spots districts (85M). Despite efforts to limit their number, some disease outbreaks, such as cholera, malaria, and measles, continue to have a burden in terms of morbidity and mortality. In contrast, others, such as poliomyelitis, yellow fever and diarrhoeal disease, have shown a declining trend, and wild polio virus transmission has been eliminated in the region. Results suggest that concerted public health action may help reduce outbreaks in the region. Results can be used to inform preparedness and prevention activities. Priority public health actions should target DRC and Nigeria and identified hot spots and areas with existing risk factors within other countries.